Simultaneous Hydrolysis-Leaching Of Synthetic Manganese Ore Using Bamboo Saw Dust And Computational Analysis Using Ansys - Perumal, Suchitra (Universiti Sains Malaysia, 2018)
This research is carried out to investigate the main effect and interaction effect of sulphuric acid concentration and rotation speed of stirrer on SMO by using Minitab 18 and to study the flow behaviour of BSD, SMO and sulphuric acid using ANSYS Fluent software. Prior to the experimental work, sample preparation and characterization studies are carried out. The BSD and SMO particle size were reduced to -75 µm. XRF analysis indicates that the major elements present in SMO are Mn (68.490 %), and Fe (0.06 %) while the minor elements are Ca (0.00393 %) and K (0.000623 %). From the XRD result, BSD is found out to have 41.01 % of crystallinity. Simultaneous hydrolysis-leaching process of SMO is conducted with full factorial design of 22+ 5. The two factors are studied in this research which are the concentration of sulphuric acid and rotation speed of stirrer. High, medium and low level of the variable are indicated by +1, 0 and -1 respectively. Five centre points are added in this design as a measurement in process stability and to check curvature. The Mn recovery from the leached liquor is determined by using ICP-OES. Then, main effect and interaction effect of the variables on experimental work is analysed by using Minitab 18. For the computational work, first reaction flask model were designed using Solid Works 2013. This model was imported into ANSYS Fluent 15.0. The flow behaviour of air, solid and liquid phases during simultaneous hydrolysis-leaching were analysed at different stirring speed. The mathematical model generated using ANOVA shows no significance effect was shown between the main variables on the experimental work. However, the interaction effects between main variables are quite significant. From the computational analysis, flow behaviour at 400 rpm is more turbulent and the solid and liquid phases are well-distributed than at 200 rpm. Medium level of distribution is shown at 300 rpm.